Peers in the Role of Shaping Student Morals at MAN 2 Lamongan - Della Intan Sari; Nabila Qurota A'yun; Rizka Norma Nadhiroh; Rachmatul Laila Nur Anggraini (AJER: Advanced Journal of Education and Religion, 2024)
Peer groups play a crucial role in shaping the character of students at MAN 2 Lamongan. Interaction with peers helps develop noble social attitudes and molds their character and good moral conduct. The aim of this research is to explore the moral education taught at MAN 2 Lamongan and the role of peers in forming students' morals at the institution. This study employs a qualitative method with a descriptive approach, utilizing data collection techniques such as observation, interviews, and documentation. The findings indicate that the moral education provided at MAN 2 Lamongan is effective with the appropriate educational methods, while peers significantly influence students' moral development. Choosing good and high-quality peers positively impacts students' behavior and morality, whereas associating with peers with poor moral conduct can have negative consequences. Therefore, it is crucial for students to select peers who exhibit good and positive moral values.